On Stalin's team: The years of living dangerously in Soviet politics. Issue 3 (December 2015) - Fitzpatrick, Sheila
Abstract : Sheila Fitzpatrick offers a brief tour of her new book, which takes an insistently humanising view of Stalin and the group of men who supported his leadership and later succeeded him.